KARAKTERISTIK MORFOLOGI DAN KIMIA TANAH PADA LAHAN PERTANAMAN PADI LADANG DI KABUPATEN BUTON UTARA - LA ODE RUSTAM; SYAMSU ALAM (Fakultas Pertanian Universitas Halu Oleo, 2023)
Soil characteristics determine the potential yield of cultivated plants. Soil morphological characteristics generally differ between depths and locations, so different management efforts are required. This study aimed to determine the morphological characteristics of the soil in each layer and between sub-districts on upland rice cultivation land in North Buton Regency. The research method is based on free survey observations with an area administration approach to upland rice cultivation. Soil observation is carried out by drilling. Drilling is carried out to a depth of 120 cm or up to a layer of soil parent material. Qualitative soil descriptions have been carried out directly in the field to obtain an overview of soil morphological characteristics between layers and locations. The results showed the morphological characteristics of the soil on upland rice cultivation in North Buton Regency, where soil colors are generally brown (ranging from dark brown to yellowish brown; Hue 7.5-10 YR with low value and chroma respectively). Soil texture generally includes fine to medium texture, ranging from clay, silt to loam, except for the slightly coarse-textured Bonegunu area (sandy loam) in the subsoil layer. Soil consistency generally includes firm in moist conditions, plastic and sticky in wet conditions. Soil organic matter content is generally moderate, except for the Kambowa area which is low. While the soil pH levels, both between depths and locations, are in the slightly acidic category. It is necessary to pay attention to the differences in pedogenesis factors between locations in the management of upland rice cultivation in the North Buton Regency to realize optimal and sustainable productivity.